Photoinduced Structural Dynamics in Noble Gas Solids - Martínez Mesa, A.; Uranga Piña, L. (Revista Cubana de Física, 2012)
The investigation of the structural properties and the photoinduced relaxation dynamics of noble gas matrices and clusters has experienced an accelerated progress during the last two decades. The marked sensibility of the electronic states of the impurity to the modifications in the environment enables the accurate characterization of the time-evolution of the dynamical processes in condensed phase. Noble gas systems at low temperature, apart from their great advantages for molecular spectroscopy studies, exhibit unique properties from the fundamental point of view, derived from the significant influence of quantum delocalization effects on the dynamics of the system. In this review, an overview is presented of some of the experimental and theoretical tools used nowadays, in the study of the geometrical rearrangement and the mechanisms of energy transfer into the medium, as well as several illustrative examples that have contributed, in recent years, to shape our understanding of these phenomena.